LINKING ESG AND CREDIT RISK: EVIDENCE ON FINANCIAL PERFORMANCE AND STOCK MARKET RETURNS IN ASEAN BANKING SECTOR - Anita, Anita; Sibarani, Blasius Erik; Alamin, Ahmad Fikri (International Journal of Application on Economics and Business, 2025)
This research seeks to examine the influence of Environmental, Social, and Governance (ESG) factors and Non-Performing Loans (NPLs) on financial performance and their effects on stock returns within the ASEAN banking industry. The impetus for this study arises from the growing emphasis on sustainability in the financial sector and the difficulties presented by credit risk, both of which are vital elements influencing bank performance and appeal to investors. The study population consists of banking institutions from five ASEAN nations—Indonesia, Malaysia, Singapore, Thailand, and the Philippines—over the period of 2021–2023. A total of 102 valid observations were gathered through purposive sampling following the outlier examination. The variables analyzed consist of ESG, NPL, financial performance assessed by Return on Assets (ROA), and stock returns, all obtained from Bloomberg. Analysis was conducted with SmartPLS software. The results show that ESG has a positive and significant effect on both financial performance and stock returns, whereas NPLs have a negative and significant effect on these results. Conversely, stock returns are not notably influenced by financial performance. These findings indicate that ASEAN investors prioritize factors beyond profitability, emphasizing the significance of sustainability practices, effective governance, and management of credit risk. This study adds to the existing literature by supporting stakeholder theory, which asserts that the success of a corporation depends on harmonizing the interests of all stakeholders. The results urge banks to strengthen ESG practices and refine credit risk management to enhance performance and sustain investor trust in the capital markets.